SYSTEM AND GENESIS OF ETHNIC DIASPORA CULTURE - Yessim, G.; Sarkulova, M.S.; Amen, A.Zh. (Scientific Journal of Pedagogy and Economics, 2020)
The problem of the historical formation of the culture of ethnic groups and the identification of their specific features is very urgent, since the diaspora culture is able to significantly transform depending on environmental conditions, among which socio-economic and ethnopolitical ones can become decisive. The result of transformational processes in each case can be individual, therefore, studies of specific conditions and the specifics of the formation of a culture of ethnic diasporas are quite significant. A theoretical study of the features of the historical formation of the culture of various resettlement groups makes it possible to identify possible common structures in the model for studying such phenomena, to study the features of intercultural dialogue of diasporas, and, as a result, to predict the results of intercultural dialogue of diasporas with the environment, thereby ensuring the comfortable functioning of the diaspora culture as a whole. The relevance of the topic in practical terms is caused not only by the increased needs of representatives of different ethnic groups and diasporas to preserve their culture, but also by the desire for its development, the formation of stability in it. The article builds the logic of the concepts of culture-ethnic culture - culture of the ethnic Diaspora. The culture of the ethnic Diaspora is studied as a specific way of people's activity to preserve and create a set of cultural elements and structures that have ethnic specificity, and by performing ethno differentiating and ethno integrating functions, contribute to the awareness of their unity by various, often dispersed, parts of a particular ethnic group. The article describes the features of implementing the main functions of the culture of the ethnic Diaspora: ontological, aesthetic, sociological, historical, reflexive, axiological, ethical, communicative, and psychotherapeutic.